Altered landscape of total RNA, tRNA and sncRNA modifications in the liver and spleen of mice infected by Toxoplasma gondii. - Xiao-Xuan Zhang; Yu-Zhe Sun; Wei Wang; Yang Gao; Xin-Yu Wei; Hong-Chao Sun; Chun-Ren Wang; Hong-Bo Ni; Xing Yang; Hany M Elsheikha; Huan-Ping Guo (Public Library of Science (PLoS), 2024)
Background Pathogens can impact host RNA modification machinery to establish a favorable cellular environment for their replication. In the present study, we investigated the effect of Toxoplasma gondii infection on host RNA modification profiles and explored how these modifications may influence the host-parasite interaction. Methodology/principal findings We analyzed the modification levels of ∼ 80 nt tRNA and 17-50 nt sncRNAs in mouse liver, spleen, and serum using liquid chromatography and tandem mass spectrometry analysis. The results revealed alterations in RNA modification profiles, particularly during acute infection. The liver exhibited more differentially abundant RNA modifications than the spleen. RNA modification levels in serum were mostly downregulated during acute infection compared to control mice. Correlations were detected between different RNA modifications in the liver and spleen during infection and between several RNA modifications and many cytokines. Alterations in RNA modifications affected tRNA stability and protein translation. Conclusions/significance These findings provide new insight into the role of RNA modifications in mediating the murine host response to T. gondii infection.